Comparison of the Effectiveness of Schema Therapy and Cognitive Behavioral Therapy on Anger Management, Emotion Regulation, and Heart Rate Variability in Women Experiencing the Psychological Consequences of the 12-Day War in Hamedan - Yaghoobi, Abolghasem; Meysam, Samaneh; Eftekhari, Asma; Asgari, Fatemeh; Ebrahimkhani, Mehdi (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The objective of this study was to compare the effectiveness of Schema Therapy and Cognitive Behavioral Therapy (CBT) on anger management, emotion regulation, and heart rate variability in women affected by the psychological consequences of the 12-day war in Hamedan. Methods and Materials: This randomized controlled trial was conducted on 45 women experiencing war-related psychological distress in Hamedan, who were randomly assigned to Schema Therapy (n = 15), CBT (n = 15), or a control group (n = 15). Both intervention groups received ten weekly 90-minute group therapy sessions, while the control group received no intervention during the study period. Participants completed standardized measures of anger management and emotion regulation, and heart rate variability was recorded using a standardized ECG protocol at pretest, posttest, and five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS-27. Findings: Repeated measures ANOVA revealed significant main effects of time and significant time × group interactions for anger management (F = 38.45, p < .001, η² = .79), emotion regulation (F = 34.39, p < .001, η² = .77), and heart rate variability (F = 32.57, p < .001, η² = .76). Bonferroni comparisons indicated that both Schema Therapy and CBT significantly outperformed the control group on all outcome variables at posttest and follow-up (all p < .001), while Schema Therapy produced significantly greater improvements than CBT across all variables at follow-up (p values .008–.012). Conclusion: Both Schema Therapy and CBT were effective in improving emotional and physiological functioning among war-affected women, with Schema Therapy demonstrating superior and more durable therapeutic effects.